A patient-centered clinical interview script for medical undergraduate teaching - Wenceslau, Leandro David (2020)
The teaching of clinical communication skills in medical undergraduate studies finds in the principles and components of the Patient-Centered Clinical Method (PCCM) an important reference to define its competences. However, even having contact with the PCCM in undergraduate teaching, medical students often resort to the traditional medical doctor-centered anamnesis as a safer script for conducting their interviews. We propose, as a hypothesis for this difficulty, the absence of a PCCM translation into a standardized medical interview script, especially for undergraduate teaching. In this report, based on patient-centered clinical interview (PCCI) models selected from the international literature, we present the first step of an original PCCI script, adapted for the Brazilian scenario. This report aims to provide a user-friendly reference in Portuguese that can be improved by professionals involved with the teaching of clinical communication skills in higher education in Brazil. Empirical studies are still needed to support wider use of the proposal presented here.